INVENTORY APPLICATION DESIGN AT INDUSTRIAL WATER DEPO USING EXTREME PROGRAMMING METHOD - Marco Antonio Narahaba; Francka Sakti Lee (Jurnal Techno Nusa Mandiri, 2024)
Bening Water Depo involves in selling mineral water and refill water and trading with partner entities in the water sector. In the activities of inventory management and storage as well as recording of sales, problems are found because the management of inventory recording and recording of sales made in stores often experiences data loss caused by inventory recording still in paper form or you can say it is still doing manual recording, which has the possibility of collecting lost, damaged paper, or the recorded data cannot be read clearly. The urgency is to track expenses and income if the activity in the store is too crowded and records are still in paper form. The Extreme Programming method is used in this study. Steps of the extreme programming methodology cover the application planning phase, the application design phase, the application coding phase, and finally the application testing phase by doing blackbox testing to test the functional of the system. Results of this study are a website-based inventory application with several types of features including incoming and outgoing data management, then recording goods data, customer recording, recording incoming goods transactions, outgoing transaction reports, incoming goods reports, commodity data reports, customer data reporting, as well as book reports that include sales transaction reports, reseller sales reports, and purchase or restock reports. Implementing an inventory application in a gallon drinking water business can increase operational efficiency, improve customer service, and help in making better decisions for sustainable business growth.